Cicatricial ectropion surgery: a prospective study of long‐term symptom control, patient satisfaction and anatomical success. (8th July 2018) - McKelvie, James; Papchenko, Taras; Carroll, Stuart; Ng, Stephen GJ
Abstract: Importance: Cicatricial ectropion repair is effective and has a low complication rate. Background: To evaluate the effectiveness and long‐term functional outcomes of surgical repair of lower lid cicatricial ectropion. Design: Prospective consecutive case series. Participants: Forty‐four consecutive operations for cicatricial ectropion repair. Methods: Consecutive cases of cicatricial ectropion repair completed during 2007–2011 in Waikato Hospital and Hamilton Eye Clinic, New Zealand, were enrolled in the study following formal ethics approval. Ectropion repair was completed using inferior retractor repositioning, horizontal lid tightening and full‐thickness skin grafting. Main Outcome Measures: Patient‐reported symptoms and satisfaction, ectropion recurrence and punctal ectropion. Results: Forty‐four eyes of 40 patients (30 males and 10 female) were included in the study. The average age at surgery was 75 years. Watering and poor appearance were the most common presenting symptoms. Postoperative follow‐up was 1–6 years (mean = 4 years). There were no major perioperative complications, one patient developed trichiasis postoperatively. There were five reoperations (11%) during the study period. Two patients underwent medial spindle procedures for symptomatic medial ectropion and three patients required additional horizontal lid tightening. Seventy percent of patients reported satisfaction with their long‐term results despite the partial recurrence of symptoms in 45%. Ectropion recurrence in <1 year occurred in three patients. Conclusion and Relevance: In this series, satisfactory appearance and symptom control were reported by 68% of patients at long‐term follow‐up. Preoperative marked ectropion with marked lid laxity is associated with early treatment failure and may be regarded as a relative contraindication to surgical correction with this technique. Punctal ectropion is an unreliable indicator of functional success.